Trends in Complementary and Alternative Medicine Use among Patients with Prostate Cancer - Zuniga, Kyle B; Zhao, Shoujun; Kenfield, Stacey A; Cedars, Benjamin; Cowan, Janet E; Van Blarigan, Erin L; Broering, Jeanette M; Carroll, Peter R; Chan, June M (The Journal of urology, 2019)
We explored the prevalence and trends of self-reported complementary and alternative medicine use among patients with prostate cancer using CaPSURE™ (Cancer of the Prostate Strategic Urologic Research Endeavor). A total of 7,989 CaPSURE participants completed questionnaires between 1996 and 2016 on the use of nearly 70 complementary and alternative medicine types. Participants were defined as users if they indicated that they had ever used complementary and alternative medicines. To evaluate trends among 7,696 patients with newly diagnosed prostate cancer we considered complementary and alternative medicine use within 24 months of diagnosis and calculated the percent change in complementary and alternative medicine use between groups defined by the year of diagnosis. Of patients with prostate cancer 56% reported complementary and alternative medicine use on at least 1 questionnaire. Multivitamin and omega-3 fatty acid use was common at 40% and 24% of patients, respectively. Compared to nonusers greater proportions of complementary and alternative medicine users were college educated, had a higher household income and lived in the West and Midwest. Median prostate specific antigen at diagnosis was 5.8 (IQR 4.4-8.4) and 6.2 ng/ml (IQR 4.7-10.1) among users and nonusers, respectively (p <0.01). Between those diagnosed in 1996 to 2000 and 2011 to 2016, complementary and alternative medicine use increased 128% from 24% to 54%. When comparing participants diagnosed in 2006 to 2010 with those diagnosed in 2011 to 2016, a 108% increase was seen in supplemental vitamin D use and a -48% decrease was seen in supplemental vitamin E use. Many patients with prostate cancer reported complementary and alternative medicine use. Multivitamins and omega-3 fatty acids were commonly ingested and vitamin D use increased dramatically from 2006 to 2010 compared to 2011 to 2016. These data can guide clinical discussions and decision making such as nutritionist referral and help prioritize future research.